PERAN PEMERINTAH DAERAH DALAM PENGEMBANGAN KEAMANAN MARITIM INDONESIA - GPH Dipokusumo, Karya Sukrilawati, Christy Damayanti & (Transformasi, 2018)
This research described and analyzed a problem concerning the role of local government in safeguarding maritime security from illegal fishing in Natuna Sea through maritime diplomacy. The objective of research was to analyze the role of local government in maritime diplomacy as an attempt of safeguarding its maritime area during 2015-2017. The research method employed was qualitative one with primary and secondary data. Data collection was carried out using interview and documentation methods. From the research on the role of local government in maritime diplomacy, it could be found that the role of local government in maritime diplomacy was passive in nature, because the local government’s authority was to apply the policies resulting from maritime diplomacy in its area. Natuna Regency Government in developing maritime security served as policy initiator intended to Central Government, and then implemented those policies by conducting socialization, fishermen empowerment and fish and seaweed cultivation.Keywords: Maritime Security, Maritime Diplomacy, Local Government Role, Natuna Sea